The Influence of Family Support and Locus Control On Resilience of Bullying Victims - Crisna, Ghifaris Ramthunder; Mahmudi, Ibnu; Christiana, Ratih (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2020)
This article aims to conduct in order to obtain clarity and objective information regarding the correlation between family support and locus of control to bullying victim resilience in seventh-grade student junior high school at SMP 1 Kampak. The research method used ex post facto correlational descriptive. The population is 240 students. The sample consisted of 30 students with purposive sampling. in the form of questionnaires with Likert scale results of validity and reliability were obtained : (1) 28 item valid, Cronbach alpha =0.917, (2) 29 item valid, Cronbach alpha =0.926, and (3) 29 item valid, Cronbach alpha =0.930.%. Data instrument analysis used product-moment correlation and regression. The statistic result : (1) tcount=5.801 > ttable=2.048 it means there is an effect of family support to the resilience of bullying victims, (2) (1) tcount=15.686> ttable=2.048 it means there is an effect of locus of control to the resilience of bullying victims, and (3) fcount =118.741> ttable=3.354 and significant value 0.000 <0.05The conclusion is that there is a simultaneous effect of family support and locus of control on the resilience of bullying victims in seventh-grade student junior high school at SMP 1 Kampak Trenggalek District. Besides that, to producing a valid and reliable measurement scale of family support, locus of control, and resilience, the theoretical findings in this study are able to provide information on several indicators that affect the resilience of victims of bullying.